2021
DOI: 10.3390/molecules26247643
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Investigation in Neuroprotective Effects of the GPR55 Ligand VCE-006.1 in Experimental Models of Parkinson’s Disease and Amyotrophic Lateral Sclerosis

Abstract: Cannabinoids act as pleiotropic compounds exerting, among others, a broad-spectrum of neuroprotective effects. These effects have been investigated in the last years in different preclinical models of neurodegeneration, with the cannabinoid type-1 (CB1) and type-2 (CB2) receptors concentrating an important part of this research. However, the issue has also been extended to additional targets that are also active for cannabinoids, such as the orphan G-protein receptor 55 (GPR55). In the present study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…They observed a beneficial neuroprotective effect on dopaminergic neurons injured by 1methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and an anti-inflammatory and anti-cataleptic effect as a result of GPR55 activation in parkinsonian mice models. Burgaz et al (2021) found similar results in two PD models, which revealed the neuroprotective effect of VCE-006.1, which is a chromenopyrazole derivative with biased orthosteric and positive allosteric modulator effects on GPR55. They found that the drug reversed motor dysfunction, the loss of tyrosine hydroxylase-containing neurons, and the elevated glial reactivity detected in the SNpc of parkinsonian mice.…”
Section: Introductionsupporting
confidence: 62%
“…They observed a beneficial neuroprotective effect on dopaminergic neurons injured by 1methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and an anti-inflammatory and anti-cataleptic effect as a result of GPR55 activation in parkinsonian mice models. Burgaz et al (2021) found similar results in two PD models, which revealed the neuroprotective effect of VCE-006.1, which is a chromenopyrazole derivative with biased orthosteric and positive allosteric modulator effects on GPR55. They found that the drug reversed motor dysfunction, the loss of tyrosine hydroxylase-containing neurons, and the elevated glial reactivity detected in the SNpc of parkinsonian mice.…”
Section: Introductionsupporting
confidence: 62%
“…Recovery of dopamine depletion is observed when rats were treated with AM404 but not with UCM707, indicating antioxidant properties of phytocannabinoid molecules/analogue behind the neuroprotective role against PD which is further confirmed by upregulation of superoxide dismutase, a key endogenous enzyme against oxidative stress. It is worth mentioning that a recent study by the same group using a similar 6-HDA-induced cellular and murine model of PD demonstrates that the quinone derivative of CBD exhibits its neuroprotective behavior via PPAR-γ receptors ( Burgaz et al, 2021 ). Furthermore, recently, Giuliano et al have demonstrated that a higher dose of CBD (10 mg/KgBW) can reduce nigrostriatal degeneration and improve motor function in rats bearing 6-HDA-induced PD ( Giuliano et al, 2021 ).…”
Section: Disease-specific Pathwaymentioning
confidence: 99%
“…In particular, PPARα can be activated in vitro by the eCB-like compound PEA, leading to an increase in CB 2 R expression and 2-AG production ( Guida et al, 2017 ), and the migration capacity of these cells ( Franklin et al, 2003 ; Guida et al, 2017 ). The orphan receptor GPR55 is also expressed in microglia and is attracting special attention in different neuroinflammatory pathologies ( Marichal-Cancino, 2017 ; Saliba et al, 2018 ; Burgaz et al, 2021 ). This receptor appears to follow a similar expression pattern to CB 2 R when microglia are stimulated with LPS.…”
Section: Microgliamentioning
confidence: 99%